2011
DOI: 10.1002/j.0022-0337.2011.75.8.tb05157.x
|View full text |Cite
|
Sign up to set email alerts
|

Treating Patients with HIV and Hepatitis B and C Infections: Croatian Dental Students’ Knowledge, Attitudes, and Risk Perceptions

Abstract: Dentists and dental students can be exposed to the human immunodeiciency virus (HIV), hepatitis B virus (HBV), and hepatitis C virus (HCV) during routine work. The aims of this study were to assess a group of dental students' knowledge about HIV, HBV, and HCV infections; assess their attitudes and risk perceptions about the treatment of patients with HIV, HBV, and HCV; and identify factors associated with their knowledge and willingness to treat these patients. An anonymous survey was administered to 534 predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 12 publications
4
22
1
3
Order By: Relevance
“…10 Dentists may be concerned and reluctant because of risk for contamination while treating hepatitis B virus, hepatitis C virus and HIV positive patients. 11 These concerns may be originating from the knowledge deficiency about these diseases in some dentists. 11,12 In our country, several studies have evaluated the awareness level and behaviours of the dentists about some contagious diseases, 13 exposure frequency to infection in dentists 14 and use of personal protective equipment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Dentists may be concerned and reluctant because of risk for contamination while treating hepatitis B virus, hepatitis C virus and HIV positive patients. 11 These concerns may be originating from the knowledge deficiency about these diseases in some dentists. 11,12 In our country, several studies have evaluated the awareness level and behaviours of the dentists about some contagious diseases, 13 exposure frequency to infection in dentists 14 and use of personal protective equipment.…”
Section: Introductionmentioning
confidence: 99%
“…11 These concerns may be originating from the knowledge deficiency about these diseases in some dentists. 11,12 In our country, several studies have evaluated the awareness level and behaviours of the dentists about some contagious diseases, 13 exposure frequency to infection in dentists 14 and use of personal protective equipment. 15 However, there is no comprehensive study in the literature which analysed the exposure rate of the Turkish dentists to infection, their knowledge level about standard precaution and practices after exposure to hepatitis B virus, hepatitis C virus, HIV infections, and their attitudes and behaviours in an integrated approach.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike this research, studies that investigated the knowledge of dental students about HIV / AIDS [25][26][27] and occupational of blood-borne pathogens [28,29] showed that knowledge about some aspects was greater among students with higher educational level. Keser et al [25] justi ed this nding by the fact that the older group may have gained more experience over the years and was exposed to larger number of patients compared to the younger group.…”
Section: Discussionmentioning
confidence: 56%
“…Keser et al [25] justi ed this nding by the fact that the older group may have gained more experience over the years and was exposed to larger number of patients compared to the younger group. Brailo et al [29] reported that this nding can be explained by the fact that in the clinical phase, at the beginning of the clinical practice in each department, students are introduced to this content again.…”
Section: Discussionmentioning
confidence: 99%
“…they can cause serious health and life-threatening diseases. It is estimated that in the case of an injury with a hepatitis B virus contaminated needle, the probability of infection is 6-30% [27,28]. hepatitis B virus causes asymptomatic acute or chronic infections, which can lead to cirrhosis or primary liver cancer [29].…”
Section: Biological Hazardsmentioning
confidence: 99%